2012
DOI: 10.1021/ie300975h
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Solubility and Diffusivity of Gases in Polymers under High Pressure: N2 in Polycarbonate and Poly(ether-ether-ketone)

Abstract: The aim of this study was to develop a model that predicts the gas solubility and the sorption and desorption kinetics in polymer granulates over large temperature and pressure intervals. Besides the part predicting the solubility and diffusivity, the model involves the simultaneous solution of the diffusion equation and the heat equation in three dimensions using a finite element method (FEM). When the temperature-and pressure-dependent solubility of a specific polymer/gas combination is not known, an improve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 33 publications
(59 reference statements)
0
19
0
Order By: Relevance
“…They are of the same order, showing that chain motions are still possible during the sorption process, even at high pressure. In the literature, some authors reported also a decrease of gas sorption at high pressure, assigning this behaviour to a decrease of the material free volume under these conditions [20,[48][49][50]. The swelling of the polymer amorphous phase consecutively to the sorption phenomenon was then determined as a function of the gas nature and sorption conditions.…”
Section: Study Of Gas Sorption By Molecular Simulationmentioning
confidence: 99%
“…They are of the same order, showing that chain motions are still possible during the sorption process, even at high pressure. In the literature, some authors reported also a decrease of gas sorption at high pressure, assigning this behaviour to a decrease of the material free volume under these conditions [20,[48][49][50]. The swelling of the polymer amorphous phase consecutively to the sorption phenomenon was then determined as a function of the gas nature and sorption conditions.…”
Section: Study Of Gas Sorption By Molecular Simulationmentioning
confidence: 99%
“…T g data was obtained from Condo and Johnston (1994). Diffusivity of CO 2 is the polymer was obtained from Nilsson et al (2013). Viscosity as a function of shear rate was obtained using a sliding plate rheometer and fit to a Cross model given in Equation 6.…”
Section: Physical Propertiesmentioning
confidence: 99%
“…Nilsson et al [18] measured the permeability, solubility and diffusion coefficients of nitrogen gas in polycarbonate and polyether ether ketone polymers at a pressure of 670 bar and at temperatures in the range of 100 to 250 °C. In contrast, Celina and Gillen [19] used a continuous flow method for measuring the permeability of oxygen through elastomers at pressures of approximately 315 mm Hg and temperatures of 225 °C.…”
Section: Introductionmentioning
confidence: 99%